The periosteal pulley technique for orbital fat realignment and correction of nasojugal groove in lower lid blepharoplasty - Kamol Wattanakrai (2018)
Background: Removal of orbital fat in lower lid blepharoplasty has been widely replaced by fat realignment over the orbital rim. However, incomplete correction or recurrence of fat bulging is still common compared to a simple fat removal procedure due to improper transfer and fixation of fat over the orbital rim. The authors present a novel technique of orbital fat transfer under the periosteal strip to secure the fat along the orbital rim and prevent recurrence of fat bulging from reherniation. Methods: Of the patients who underwent lower blepharoplasties using the periosteal pulley technique during January 2010 to September 2012, 115 were included in this prospective uncontrolled clinical trial. There were 107 females and eight males. The follow-up period ranged from 6 months to 2 years (average 1 year). The results on the last follow-up were categorised into four grades: excellent, good, fair and poor. Result: Of the 115 patients, 10, 81 and 24 patients achieved excellent, good and fair results, respectively. We have three cases of temporary lower lid retraction or ectropion that developed 1 month after surgery and were resolved within 3-4 months. No revision surgery is needed. Conclusion: We propose the periosteal pulley technique as an alternative way of orbital fat transfer in lower lid blepharoplasty. This technique can provide a secure fixation of fat that not only corrects the nasojugal groove but also prevents further herniation of the remaining fat. © 2014 British Association of Plastic, Reconstructive and Aesthetic Surgeons. Published by Elsevier Ltd. All rights reserved.